(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
The article discusses the socio-pedagogical necessity of increasing the political activity of student youth, the factors of forming the political culture of youth, the causes and consequences of the imbalance in the development of political consciousness and political culture, and the conditions associated with the development of political activity in youth.